Iridium-catalyzed aza-spirocyclization of indole-tethered amides: an interrupted Pictet–Spengler reaction - Gabriel, P; Gregory, A; Dixon, D (American Chemical Society, 2019)
A mild, reductive spirocyclization of indole-linked amides and lactams for the efficient and selective synthesis of aza-spirocyclic indoline products is described. The catalytic reductive activation of tertiary amides or lactams by Vaska's complex with tetramethyldisiloxane as the terminal reductant allowed iminium ion formation, before a diastereoselective 5-endo-trig spirocyclization of the tethered indole moiety was triggered. Terminal reduction affords the aza-spiroindoline products in an overall highly chemoselective and diastereoselective one-pot process.